Review of the Merodon albifasciatus Macquart species complex (Diptera: Syrphidae): the nomenclatural type located and its provenance discussed - Vujić, Ante; Ståhls, Gunilla; Ačanski, Jelena; Rojo, Santos; Pérez-Bañón, Celeste; Radenković, Snežana (Zootaxa, 2018)
The Palaearctic Merodon geniculatus species group (Diptera, Syrphidae: Merodontini) currently comprises six Western Mediterranean species and four species with Eastern Mediterranean distribution. One of this group species, Merodon albifasciatus Macquart, 1842, is the only Merodon species listed from the Oriental Region. We discovered the lost holotype, which fit morphologically with European Merodon females of the M. albifasciatus species complex confirmed here and that occurs in the Palaearctic region. An integrative approach to the taxonomy of M. albifasciatus based on morphological and molecular evidences revealed the existence of two additional closely-related species in the Eastern Mediterranean area, M. luteofasciatus Vujić, Radenković & Ståhls sp. nov. and M. neofasciatus Ståhls & Vujić sp. nov.. The females of these three species can only be separated by molecular and distributional data. With the aim of stabilising species concepts within the complex, the taxon distributed in mainland Greece, including the Peloponnese was associated to the old female holotype of M. albifasciatus. The identity of Merodon fractipes Paramonov, described from Rhodes Island (Greece) as subspecies of M. geniculatus Strobl in Czerny & Strobl, could not be resolved as the type specimen is lost. Thus the name M. fractipes is suppressed as nomen dubium. We discuss the distribution of the species of M. albifasciatus complex, identify host plants of M. neofasciatus, and provide an identification key to males of Eastern Mediterranean species of Merodon geniculatus group.